Pengaruh Work from Home terhadap Work Engagement pada Karyawan yang Memiliki Anak: Peran Mediasi Work-life Balance dan Work Stress - Asya Anaya; Putri Mega Desiana (IPB University, 2023)
This study aims to investigate and determine the effect of work from home on work engagement in Greater Jakarta for employees who have children during the COVID-19 pandemic. This study also tested work stress and work-life balance variables as mediating variables using a structural equation modeling (SEM) approach. The data used was obtained through a cross-sectional survey of 213 respondents who met the criteria, namely domiciled in Greater Jakarta, are employees who formally work in companies in Greater Jakarta, have or are currently working from home and have children. The results of this study indicate that work from home has a negative effect on the work engagement of employees who have children in Greater Jakarta during the pandemic. Furthermore, work-life balance mediates the effect between work from home and work engagement partially and is competitive. In addition, work stress does not mediate the effect between work from home and work engagement. However, in this study work stress has a negative effect on work-life balance so that the effect of work stress on work engagement can be through work-life balance. This research contributes to managerial implications that can be applied by organizations, managers, individuals and other interested parties related to the concept of work from home, work-life balance, work stress, and work engagement during the COVID-19 pandemic in Indonesia, especially in Greater Jakarta.